Spectrum of Acute Complications of Measles in Erbil City - Hamad, Kawes Omer (Zanco Journal of Medical Sciences (ZJMS), 2010)
Background and objective: Measles is an infectious viral disease which is highly communicable and a notifiable disease, it is encountered as a cause of morbidity and mortality. The objective of this study was to find out the most encountered acute complications of measles and relation of these complications to the age of children and vaccination status. Methods: This is a prospective study done in Raparin pediatric teaching hospital, Erbil city, in the period of December 2008 to May 2009. Sixty eight cases of measles admitted with variable complications were studied. History was taken, complete examination and follow up in the hospital for variable complications was done. Results: The mean age was 23.28 ±18.91 months, 42 cases (61.8%) of the admitted children were two years or less. Male children were 35(51.5%) cases and female 33 (48.5%) cases. Most of affected cases were unvaccinated for measles 58 cases (85.3%), history of contact in the family was observed in 33 cases (48.5 %) while10 cases (14.7%) has contact history in the pediatric hospital and 25 cases (36.8%) didn’t show any clear contact history. The most common complications were diarrhea 45 cases (66.2%), pneumonia and vomiting 36 cases (52.9%) for each and febrile convulsions 5 cases (7.4%) and encephalitis 2 cases (2.9%). Conclusion: Children who were infected and developed complications were less than two years of age , most of them were not vaccinated and they were from rural areas.